Cloud computing and security : first International Conference, ICCCS 2015, Nanjing, China, August 13-15, 2015. Revised selected papers /: first International Conference, ICCCS 2015, Nanjing, China, August 13-15, 2015. Revised selected papers. (2015) - Unknown
No abstract available